Pharmacological Activities of Carica papaya Linn - Urooj Fatima; Sammia Shahid (Journal of Basic & Applied Sciences, 2018)
Carica papaya is a tropical fruit, present in orange red to yellow orange color. The whole plant including fruit, leaves, roots, peel, bark, seed and pulp served as medicine. It is rich in minerals, carotenoids, vitamins, alkaloids, enzymes, lycopene, and flavonoids that provide the papaya with special importance. It is used as a remedy for the treatment of many skin infections, anti fungal, anti viral infections. Its milky juice extracted and dried is used as medicine for digestive disorders and as toothpaste. Carica papaya helps in the treatment of different types of cancer, kidney infections, nervous disorders, etc. Now a days papaya is known as a nutraceutical fruit because of its multifaceted properties. The most enhanced properties of papaya are anti-fungal, anti-fertility, uretonic, anti-hypertensive, hypolipidemic, dengue fever, diuretic, anti-helmintic, wound healing, antibacterial and antitumor activities. This review summarizes the magical pharmacological benefits of Carica papaya.